Taxonomic status of the bees from French Guiana described by Jules Dominique (Hymenoptera: Apidae, Megachilidae, Halictidae) - Rasmussen, Claus; Mahé, Gilles; Hinojosa-Díaz, Ismael Alejandro (Zootaxa, 2007)
In March 1898 Abbé Jules Dominique (1838–1902; Bureau, 1903; Fig. 1) published an account of the bees collected by Constant Bar (1817–1884; Oberthür, 1888) and his family in French Guiana (Dominique, 1898). Jean M. Pérez (1833– 1914) had identified both the new and known species reported by Dominique and provided Dominique with manuscript names for the new species. While Pérez never published any of the proposed new species (Anonymous, 1917), Dominique in his account of the collection included both the manuscript names and a brief description in his own words for several of these species. Michener (1987) pointed out the taxonomic implications of this publication, in particular the potential instability to nomenclature when rediscovering names which have not been used for more than a century. While Michener considered several of Dominique’s new names valid, Moure (1967) had incorrectly regarded all of Dominique’s species of Euglossa and Eulaema as nomina nuda.